1997
DOI: 10.2136/sssaj1997.03615995006100010020x
|View full text |Cite
|
Sign up to set email alerts
|

A Model of the Physical Protection of Organic Matter in Soils

Abstract: Current computer simulation models do not treat the physical protection of organic matter in soil mechanistically. A model is presented that describes physical protection explicitly as a function of the capacity of clay particles and aggregates to hold organic matter. The net rate of decomposition of organic matter depends not simply on soil texture but on the degree to which the protective capacity of the soil is already occupied. The rate at which organic matter becomes protected depends on both the amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
201
0
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 365 publications
(229 citation statements)
references
References 0 publications
7
201
0
7
Order By: Relevance
“…They were not suggesting that all soils had a minimum of 21.1 g C kg À1 soil but that they could maintain that amount through physical stabilization. The soils in our study were generally below 10 g C kg À1 soil at all depths so, according to the model developed by Hassink and Whitmore [38], there is potential to increase the soil C contents of these soils. This was not observed in our study, where there was a loss of C by the third year as compared with pre-harvest.…”
Section: Carbon Changementioning
confidence: 75%
See 3 more Smart Citations
“…They were not suggesting that all soils had a minimum of 21.1 g C kg À1 soil but that they could maintain that amount through physical stabilization. The soils in our study were generally below 10 g C kg À1 soil at all depths so, according to the model developed by Hassink and Whitmore [38], there is potential to increase the soil C contents of these soils. This was not observed in our study, where there was a loss of C by the third year as compared with pre-harvest.…”
Section: Carbon Changementioning
confidence: 75%
“…The physical capacity of a soil to protect organic matter is dependent on soil texture and the amount of organic matter already protected (i.e., stabilized) [18,32,37,38]. Hassink and Whitmore [38] developed a model relating the physical protection of organic matter to soil texture.…”
Section: Carbon Changementioning
confidence: 99%
See 2 more Smart Citations
“…This low density of complexes provides an explanation for the observed decrease in soil density with increasing concentration of OM. The complexing stabilizes the clay and thereby gives it a degree of protection against dispersion in water Emerson et al, 1986;Hassink and Whitmore, 1997). Dexter et al (2008) showed that, whereas non-complexed clay disperses readily in water, the complexed clay does not.…”
Section: Introductionmentioning
confidence: 99%